The evolving role of public libraries in South Africa in addressing information poverty: A historical context. Issue 6 (13th August 2018) - J. Strand, Karla; Britz, Johannes
Abstract : Purpose: The purpose of this paper is to provide an overview of the historical development of libraries in South Africa against a backdrop of poverty and social inequality. In particular, this paper illustrates how the development of libraries in South Africa both reflected and influenced information poverty and has as its goal to increase awareness of the role of libraries in the alleviation of information poverty. Design/methodology/approach: The information in this paper is based on doctoral research completed by the author who investigated the role of libraries in the alleviation of information poverty in South Africa. The methodology for the research included two case studies, interviews, examination of library records, and observation. An extensive review of the professional literature and recorded histories provided imperative context for that research and this paper. Findings: Findings indicate that libraries can play an important role in the alleviation of information poverty in South Africa. Libraries are underutilized in this role and in order to increase their capacity in addressing information poverty, one should consider the historical circumstances behind the dispossession of library services. Understanding the development of libraries in South Africa and sociopolitical ramifications of this development can encourage and inform greater participation of libraries in the alleviation of information poverty in the future. Originality/value: This paper compiles the work and findings of previous studies on the history of South African libraries. The information provided here offers an accessible and efficient history of libraries in South Africa. In so doing, it provides context that is invaluable to the understanding of how the development of libraries throughout time can have sociopolitical effects on the people and their circumstances. The paper also encourages increased understanding of the value and purpose of libraries in combating information poverty in South Africa.